Salivary biomarkers related to potentially malignant disorders and oral carcinomas: Brief update - Marinho, Sandra Aparecida; Agripino, Gustavo Gomes; Carvalho , Sérgio Henrique Gonçalves de; Sarmento, Dmitry José de Santana; Oliveira, Pierre Andrade Pereira de (Seven Editora, 2023)
Early diagnosis of oral cancer can improve the quality of life and increase the survival rate of patients. Saliva is a biological fluid of non-invasive access and easy collection, in which it is possible to detect proteins that play an important role in the discrimination of diseases. The presence of salivary protein biomarkers, such as cytokines (IL-6, IL-8, TNF-α)), may aid in the early diagnosis of malignant changes and may be an indicator of the presence of potentially malignant disorders and oral carcinoma. However, due to the variability of the methodologies of the different studies, the absence of standardization of saliva collection, the lack of consensus on the concentration of biomarkers, and also the absence of multicenter studies with larger samples, the reality of clinical use of these biomarkers for early diagnosis of oral cancer is still for the near future. DOI:https://doi.org/10.56238/globalhealthprespesc-001